2013
DOI: 10.1002/jor.22488
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transfer sites for flexor digitorum longus in a cadaveric adult acquired flatfoot model

Abstract: Posterior tibialis tendon (PTT) dysfunction (PTTD) is associated with adult acquired flatfoot deformity. PTTD is commonly treated with a flexor digitorum longus (FDL) tendon transfer (FDLTT) to the navicular (NAV), medial cuneiform (CUN), or distal residuum of the degraded PTT (rPTT). We assessed the kinetic and kinematic outcomes of these three attachment sites using cadaveric gait simulation. Three transfer locations (NAV, CUN, rPTT) were tested on seven prepared flatfoot models using a robotic gait simulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 26 publications
(53 reference statements)
3
24
0
Order By: Relevance
“…In considering the generally non‐significant effects of standard FDL tendon transfer, our results are consistent with previous studies which concluded that the procedure appears to have only a minor effect on altering pedobarographic parameters in the absence of a concomitant bony procedure . Uniquely, PEM‐enhancement enabled expected pedobarographic and kinematic differences not seen by previous investigators . Additionally, these differences compare to those found by other studies which applied combined procedures to achieve desired changes …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In considering the generally non‐significant effects of standard FDL tendon transfer, our results are consistent with previous studies which concluded that the procedure appears to have only a minor effect on altering pedobarographic parameters in the absence of a concomitant bony procedure . Uniquely, PEM‐enhancement enabled expected pedobarographic and kinematic differences not seen by previous investigators . Additionally, these differences compare to those found by other studies which applied combined procedures to achieve desired changes …”
Section: Discussionsupporting
confidence: 90%
“…). In comparison to previous biomechanical flatfoot studies, our methods produced greater average changes across radiograph measures and showed comparable RGS validation metrics …”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The simulation of the stance phase was 2.7 s but the reproduced GRF was smaller than the actual value. [32][33][34][35][36][37][38] Besides that, the earliest passive simulator was designed in 2003 and there was no further development in the follow-up. 39,40 Another passive simulator, UMS, was designed in 2009 and applied to investigate the biomechanical behaviors of a diabetic foot.…”
Section: Introductionmentioning
confidence: 99%